Évaluer les gains langagiers dans le cadre d’un apprentissage informel à l’étranger - Eva Donohoe (Recherches en didactique des langues et des cultures)
The purpose of this article will be to present the tools we tested to assess English skills developed through informal learning, in particular abroad. The evaluation of language gains due to informal learning is a particularly complex operation but, as Kusyk (2020 : 347) states, it is incumbent upon informal L2 researchers to identify “robust and reliable methods of measuring informal L2 change” that can be replicated in future studies. We are currently conducting a study on the impact of informal learning on the language skills of French-speaking engineering students while abroad. As part of this study, we have had to examine the evaluation methods available to us to find the one that is best suited to our students' learning contexts and to the needs of our study. This article will first present a discussion of "the difficult work of shedding light on informal learning" and the ensuing difficulty in evaluating it (Schugurensky, 2007 : 17). This will be followed by a presentation of the work that has already been conducted in France on informal learning. Afterwards, a brief review of Study Abroad research will be presented. In the final section, we will present the evaluation tools, the Versant English Placement Test (VEPT) and an analysis of oral production conducted using a framework based on complexity, accuracy, and fluency (CAF), followed by the presentation of the results of our tests. The VEPT showed an overall decrease of 7.59% in oral production, in contrast to the CAF analysis, which revealed significant gains in fluency and accuracy for students who went abroad. After examination of the test results, the analysis of oral production using the CAF framework has shown to be the preferred evaluation method as it enables us to build a more complete and more accurate picture (Kusyk 2017: 108) of the L2 development process.